2018
DOI: 10.1016/j.neo.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factors Modify Collagen I Fibers in MDA-MB-231 Triple Negative Breast Cancer Xenografts

Abstract: Hypoxia inducible factors (HIFs) are transcription factors that mediate the response of cells to hypoxia. HIFs have wide-ranging effects on metabolism, the tumor microenvironment (TME) and the extracellular matrix (ECM). Here we investigated the silencing effects of two of the three known isoforms, HIF-1α and HIF-2α, on collagen 1 (Col1) fibers, which form a major component of the ECM of tumors. Using a loss-of-function approach for HIF-1α or 2α or both HIF-1α and 2α, we identified a relationship between HIFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
(80 reference statements)
2
20
0
Order By: Relevance
“…Of the other identified proteins associated with breast cancer, COL1A1 and COL1A2, the two components of type I collagen, were shown to be upregulated in invasive breast cancer, with a potential role in spinal metastasis, although not proposed as potential targets (40). In contrast, another study found that type 1 collagen fibers increased in human MDA-MB-231 TNBC xenograft tumors when the hypoxia factors HIF-1α or HIF-2α were downregulated (41), consistent with the earlier finding of reduced collagen fibers in hypoxic tumor regions (42), but apparently contradicting a role for type 1 collagen in TNBC invasion and metastasis. Since metastases from ER-/PR- breast tumors are reportedly less likely to be skeletal compared to those from receptor-positive tumors (43), the precise importance of COL1A1/COL1A2 upregulation in TNBC remains unclear.…”
Section: Discussionsupporting
confidence: 72%
“…Of the other identified proteins associated with breast cancer, COL1A1 and COL1A2, the two components of type I collagen, were shown to be upregulated in invasive breast cancer, with a potential role in spinal metastasis, although not proposed as potential targets (40). In contrast, another study found that type 1 collagen fibers increased in human MDA-MB-231 TNBC xenograft tumors when the hypoxia factors HIF-1α or HIF-2α were downregulated (41), consistent with the earlier finding of reduced collagen fibers in hypoxic tumor regions (42), but apparently contradicting a role for type 1 collagen in TNBC invasion and metastasis. Since metastases from ER-/PR- breast tumors are reportedly less likely to be skeletal compared to those from receptor-positive tumors (43), the precise importance of COL1A1/COL1A2 upregulation in TNBC remains unclear.…”
Section: Discussionsupporting
confidence: 72%
“…Tumor stiffness assessment before or during treatment was significantly associated with the response to neoadjuvant chemotherapy in breast cancer patients [35][36][37]. Production of collagen and increased collagen crosslinking in the ECM, of which collagen is a major component, in the hypoxic tumor microenvironment promote tumor stiffness, encourage tumor cell dissemination, and induce drug resistance [2,14,15,18,19,38]. Thus, tumor stiffness affects the prognostic outcomes and drug response in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Col1 degradation is mostly due to matrix metalloproteinases MMP-1 and MMP-14. 29 In a recent paper, Goggins et al 30 suggested that a decrease of MMP-1 and MMP-14 in HIF-silenced TNBC cells would prevent Col1 degradation and increase the amount of type I collagen fibers. Also, a reduction in lysyl oxidase (LOX) protein expression in HIF-downregulated tumors suggested that more non-crosslinked collagen I fibers are present despite an overall increase in fiber density.…”
Section: Discussionmentioning
confidence: 99%